Quantitative Evaluation of Gait Changes Using APDM Inertial Sensors After the External Lumbar Drain in Patients With Idiopathic Normal Pressure Hydrocephalus - He, Mengmeng; Qi, Zhenyu; Shao, Yunxiang; Yao, Hui; Zhang, Xuewen; Zhang, Yang; Shi, Yu; E, Qinzhi; Liu, Chengming; Hu, Hongwei; Liu, Jiangang; Sun, Xiaoou; et al. (Frontiers in Neurology, 2021)
Objectives: Gait and balance disturbances are common symptoms of idiopathic normal pressure hydrocephalus (iNPH). This study aimed to quantitatively evaluate gait and balance parameters after external lumbar drainage (ELD) using APDM inertial sensors. Methods: Two-minute walkway tests were performed in 36 patients with suspected iNPH and 20 healthy controls. A total of 36 patients underwent ELD. According to clinical outcomes, 20 patients were defined as responders and the other 16 as non-responders. The gait parameters were documented, and the corresponding difference between responders and non-responders were calculated. Results: When compared with healthy controls, patients with suspected iNPH exhibited decreased cadence, reduced gait speed, a higher percentage of double support, decreased elevation at mid-swing, reduced foot strike angle, shorter stride length, difficulty in turning, and impaired balance functions. After the ELD, all these manifestations except elevation at mid-swing and balance functions were significantly improved in responders. The change of Z-score absolute value in the six parameters, except for foot strike angle, was >1. No significant improvement was observed in non-responders. Conclusion: APDM inertial sensors are useful for the quantitative assessment of gait impairment in patients with iNPH, which may be a valuable tool for identifying candidates that are suitable for shunting operations.